Analisis Usaha Pengolahan Indutri Batu Bata dan Dampaknya terhadap Penyusutan Lahan Sawah di Desa Nyitdah Kecamatan Kediri Kabupaten Tabanan - DEWI, NI KOMANG NITA; ANTARA, MADE; WIDHIANTINI, WIDHIANTINI (Jurnal Agribisnis dan Agrowisata (Journal of Agribusiness and Agritourism); Vol.11, No.1, Juli 2022, 2022)
Analysis of Brick Processing Business and Its Impact on Rice Lands Conversion in Nyitdah Village, Kediri District, Tabanan Regency.  The brick industry includes a production process that converts clay into other products that have more usability. This study aims to identify the brick production process, analyze the income and feasibility of the brick processing business, and the impact of brick processing business on rice land conversion. The research location was determined purposely, namely Nyitdah Village, Kediri District, Tabanan Regency. Most people in the village work in the brick processing business and the business could be considered as a small industry. The 61 samples were determined by using simple random sampling method. The data used in this study are primary and secondary data. The results show that the brick processing business is efficient and modern. Total net income from the brick industry is IDR 9,274,499.00 / month. The brick processing business seems feasible, considering the R / C Ratio > 1 and the BEP is less than the amount of production and the price in Nyitdah Village. However, the business has an impact on rice land conversion due to the construction of brick processing plants in rice cultivated lands. The average rice land conversion that occurs in Nyitdah Village is 0.4 ha / year.